Effect of Microbial Consortia on Soil Health, Nutrient Uptake and Yield of Soybean Grown in a Vertisol of Central India - R. K. Sahu; Iram Zehra Naqvi; G. S. Tagore; Vikash; R. K. Thakur; Shailu Yadav; N. G. Mitra (International Journal of Economic Plants)
A field experiment was carried out in the research farm of the Jawaharlal Nehru Krishi Vishwa Vidhyalaya, Jabalpur, Madhya Pradesh, India during Kharif season of 2021-22. The experiment was performed with nine treatments comprised by Rhizobium, Pseudomonas, EM and their consortia with FUI and UFUI (absolute control) in randomized block design. The soybean crop was grown in the field along with recommended package of practices. The result showed that the yield of soybean was 43% higher (2351 kg ha -1) than control FUI and better uptake of N (145 kg ha-1 by seed and 125.6 kg ha-1 by straw), P (7.9 kg ha-1 by seed and 14.9 kg ha-1 by straw) and K (42.3 kg ha-1 by seed and 65.0 kg ha-1 by straw) by soybean were found due to inoculation of microbial consortia of Rhizobium, Pseudomonas and EM culture. The Physico-chemical properties (pH, EC and OC), availability of nutrients (NPK with vales of 288, 29 and 335 kg ha-1 respectively), enzymatic activities (Acid phosphatase, alkaline phosphatase and  dehydrogenase activities with values of 42.2, 69. 8 µg PNG h-1 g-1 of  soil  and 12.9 μg TPF hr-1 g-1 of soil, respectively) and microbial population (Rhizobium by 35.1×106, total bacteria by 39.3×107, fungi by 41.9×104 and actinomycetes by 38.7×103 cfu g-1 soil) in soil also improved with the same treatment as compared to FUI. It is strongly recommended that the inoculation of microbial consortia improved the soil health and soybean production too instead of single inoculation by modulating microbial population which improves the soil health by nutrient fixation, solubilization and mobilization and plant growth promotion.